European Union : Publication of Financial Sector Assessment Program Documentation-Technical Note on Cross-Border Issues, Central Counterparties, and Central Securities Depositories. (IMF Staff Country Reports; Country Report, 2013)
The analysis focuses on the effectiveness of the regulatory, supervisory, and oversight frameworks for central counterparties (CCPs) and central securities depositories (CSDs) in the European Union (EU) as these are essential for financial stability. Cooperation between authorities within and outside the EU is critical to reduce the risks related to the cross-border nature of clearing and settlement within the EU. In this context, crisis management arrangements among EU authorities are of key importance to adequately fulfill the various responsibilities that authorities may have in relation to CCPs and CSDs in crisis situations.